Acute and Subchronic Toxicity Assessment of Conventional Soxhlet Cymbopogon citratus Leaves Extracts in Sprague–Dawley Rats - Jacob Apibilla Ayembilla; Abdul Raouf Khalid; Sharif Buari Abubakari; Abdul Rashid Adams; Felix Abekah Botchway; Stephen Antwi; Phyllis Naa Yarley Otu; Michael Appiah; George Osei-Adjei; Kwame Owen Kottoh; Peace Ahiabenu-Williams; Olga Quasie (Journal of Toxicology)
Background. In Ghana, Cymbopogon citratus leaves together with guava, pawpaw, and lime are processed into a decoction to treat fever. To encourage its usage, preclinical validation of the safety profile of the plant is required. The acute and subchronic toxicities of the conventional Soxhlet ethanolic Cymbopogon citratus leaves extract in Sprague–Dawley rats were investigated. Methods. Pulverized Cymbopogon citratus leaves were extracted with 98% ethanol using the conventional Soxhlet extraction (CSE) method and dried. In the acute toxicity study, a single dose of 5000 mg/kg body weight was administered to six female Sprague–Dawley rats and 1 ml/100 g body weight normal saline to control (6) once, and signs of toxicity were observed every hour for the first 12 hr, 24 hr, and 48 hr through to 14 days. In the subchronic study, the treatment groups were administered 200 mg/kg, 600 mg/kg, and 1200 mg/kg, respectively, of the CSE C. citratus leaves extract for six weeks. Analyses were conducted on the blood, urine, and serum samples of the rats. Histopathological examination of the liver, heart, kidney, spleen, and lungs was carried out at termination. Analysis of variance (ANOVA) was performed to determine statistically significant differences between the test and control rats at P < 0.05. Results. The results revealed that there were no statistically significant differences (p > 0.05) in the urinalysis and haematological analysis between control and test rats over the treatment period. Similarly, CSE C. citratus leaves extract did not induce any significant biochemical changes in the treatment group; however, there was a weight loss effect on the treated rats. There were no noticeable morphological changes in the heart, liver, spleen, lung, and kidney of the test rats compared to the control. Conclusion. CSE ethanolic C. citratus leaves extract has a weight loss effect, and long-term administration of the extract may not cause any organ-specific toxicity to the consumers.